The Kiai’s Leadership in Harmonizing Chinese-Muslim Relations through Multicultural Islamic Education - Paisun, Paisun; Maskuri, Maskuri; Mistar, Junaidi (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This research is motivated by the dynamics of social, religious, and economic relations between Chinese and Muslim populations in Lenteng, Sumenep, which have shown the complexity and richness of intercultural interactions. The unique cultural and religious diversity in this area has presented unique challenges and opportunities to build social harmony through the leadership role of kiai in strengthening inter-community cohesion. This study uses multicultural Islamic education to examine the role of Kiai leadership in promoting unity between Chinese and Muslim populations in Lenteng Timur, Sumenep. Employing a qualitative methodology and case study framework, data were gathered via observation, interviews, and document analysis. The results indicate two principal conclusions. The Kiai utilize various strategies, such as reinterpreting religious texts within a multicultural context, differentiating between exclusive theological doctrines and inclusive social interactions, adopting a cultural perspective rooted in Madurese values, and implementing personalized approaches through interpersonal engagement. The influence of this leadership is apparent in various aspects: socially and culturally, it has promoted harmonious integration among ethnic groups; economically, it has enabled mutually advantageous relationships based on Islamic business ethics; and religiously, it has resulted in the establishment of inclusive practices characterized by distinct “boundary awareness.” This research enhances comprehension of the transformative function of religious leadership in fostering intercultural harmony using contextually relevant, faith-based educational approaches